Lindera pulcherrima var. attenuata leaves: a nutritious and economically promising staple food in the Baiku Yao community in China - Luo, Binsheng; Nong, You; Hu, Renchuan (Frontiers in Nutrition, 2023)
The Baiku Yao community in China has traditionally used the Lindera pulcherrima var. attenuate (LPA) leaves as a staple food source, diverging from the common reliance on grains and plant roots worldwide. This study comprehensively analyzes LPA’s nutritional composition and local usage practices through field observations and laboratory testing. Our results show that LPA contains significant levels of starch, protein, and dietary fiber and is rich in trace elements, vitamin E, and flavonoids. These findings not only support the community’s traditional knowledge of LPA as a valuable food and feed source but also highlight its potential as a sustainable and innovative ingredient for new food and feed products. By filling a gap in our scientific understanding of LPA, this study may contribute to developing novel and eco-friendly agricultural practices and promote regional economic growth.